Abnormal event related EEG delta coherence in Parkinson type of dementia during the visual oddball paradigm - Güntekin, Bahar; Çadırcı, Fadime; Mantar, Nagihan; Helvacı Yılmaz, Nesrin; Özer, Fahriye Feriha; Hanoğlu, Lütfü; Yener, Görsev; Başar, Erol (Elsevier Science Ltd., 2016)
[Abstract Not Available]
18th World Congress of Psychophysiology of the International Organization of Psychophysiology (IOP) -- AUG 31-SEP 04, 2016 -- Havana, CUBA
WOS: 000382408700070